2020
DOI: 10.1098/rsbl.2020.0292
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia inducible factor-1 α knockout does not impair acute thermal tolerance or heat hardening in zebrafish

Abstract: The rapid increase in critical thermal maximum (CT max ) in fish (or other animals) previously exposed to critically high temperature is termed ‘heat hardening’, which likely represents a key strategy to cope with increasingly extreme environments. The physiological mechanisms that determine acute thermal tolerance, and the underlying pathways facilitating heat hardening, remain debated. It has been posited, however, that exposure to high temperature is associated with tissue hypoxia an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 53 publications
3
20
1
Order By: Relevance
“…This is in contrast to previous studies, which have indicated that there is a relationship between these traits in a variety of species of salmonids ( Anttila et al , 2013 ; Zhang et al , 2018 ), which has been used to suggest that there may be a mechanistic link between variation in these two traits; however, these previous studies compared rank order across families or strain rather than across individuals. Similar to our findings, Joyce and Perry (2020 ) found that CT max was not correlated with hypoxia tolerance across individuals in zebrafish, further supporting the lack of direct mechanistic linkage between these traits. Indeed, evidence is accumulating that the mechanisms underlying acute upper thermal and hypoxia tolerance are likely very different ( Jutfelt et al , 2019 ; Mandic, Best, & Perry, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This is in contrast to previous studies, which have indicated that there is a relationship between these traits in a variety of species of salmonids ( Anttila et al , 2013 ; Zhang et al , 2018 ), which has been used to suggest that there may be a mechanistic link between variation in these two traits; however, these previous studies compared rank order across families or strain rather than across individuals. Similar to our findings, Joyce and Perry (2020 ) found that CT max was not correlated with hypoxia tolerance across individuals in zebrafish, further supporting the lack of direct mechanistic linkage between these traits. Indeed, evidence is accumulating that the mechanisms underlying acute upper thermal and hypoxia tolerance are likely very different ( Jutfelt et al , 2019 ; Mandic, Best, & Perry, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…The FV, PN and CL strains exhibited little post-trial mortality (1–4% depending on the strains), the BW strain exhibited intermediate mortality (~20%), whereas the HF strain exhibited extreme mortality (~55%). This high level of mortality is unusual following a CT max trial, as post-trial mortality is generally thought to be low (1–5%) in fish ( Anttila et al , 2013 ; Joyce & Perry, 2020 ; Morgan et al , 2018 ; Scott et al , 2015 ; Zhang et al , 2018 ). The main difference between our study and most others is that our fish were exposed to a hypoxia tolerance trial 2–3 weeks previous to the measurement of thermal tolerance, which might contribute to additional mortality.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The zebrafish (Danio rerio) has emerged as an indispensable model organism to explore the role of Hifs (Cai et al, 2018;Elks et al, 2015;Joyce & Perry, 2020;Pelster & Egg, 2018), in part because zebrafish lacking both Hif-1α paralogs (hif-1aa −/− and hif1ab −/− double knockout; hereafter referred to as hif-1α −/− ) are viable (Gerri et al, 2017), in contrast to the embryonic lethality observed in germline Hif-1α or Hif-2α knockout in mammals (Compernolle et al, 2002;Iyer et al, 1998;Krishnan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…As such, many fish species, including zebrafish, are well adapted to developing in hypoxic conditions (Kopp et al, 2014;Rees et al, 2001;Ton et al, 2003), which appears to mitigate them from the deleterious effects of Hif knockout. Zebrafish thus provide a unique opportunity to understand the role that Hifs play in development when survival is not compromised, although Hif-1α knockout does incur some clear phenotypes in zebrafish, including reduced hypoxia tolerance (Joyce & Perry, 2020;. Fish can specifically provide a valuable perspective in which to understand the evolutionary origins of hypoxia-dependent cardiovascular control.…”
Section: Introductionmentioning
confidence: 99%